LANGUAGE ECONOMY IN THE DIGITAL ENVIRONMENT: ABBREVIATIONS, OMISSIONS, HYBRID FORMS (Bulletin of Innovative Research, 2026)
The article examines the mechanisms of linguistic economy in digital communication based on contemporary Russian. It analyzes structural types of abbreviations, features of elliptical constructions, and the nature of hybrid forms emerging in online discourse. Particular attention is paid to pragmatic and cognitive factors of utterance reduction, as well as to the relationship between norm and usage in the digital environment.